Exploring the Healing Paths: Navigating Complementary and Alternative Medicine - Nori, Lakshmi Prasanthi; Malla, Jyothirmai; Vadapalli, Rama Rao; Bonthagarala, Brahmaiah; Dannaram, Praveen Kumar; Venkateswara Raju, Kalidindi (International Journal of Pharmaceutical Investigation, 2025)
Due to the imbalanced patient-to-healthcare professional ratios, the increased workload for those who provide care, different adverse reactions of modern medicine, the inability to completely cure long-term ailments, expensive new medications and the emergence of novel disorders, all together have recently led to alternative medicine to attract renewed public interest. Utilizing complementary and alternative therapies can be beneficial for certain individuals. Alternative and complementary therapies are not included in standard medical care. Alternative, complementary, or integrative are terms utilized to explain medical procedures which are not considered to be a division of conventional Western medical practice. Alternative therapy comprises a wide range of disciplines, covering everything from your nutrition and exercise routine to your lifestyle and mental preparation. Herbal medicines, yoga, aromatherapy, dietary supplements, exercise, etc., are an example of alternative therapeutics.
Keywords: Alternative medicine; Cardiovascular diseases; Complementary medicine; Diabetes; Mental health issues; Regulations